Meditations to change your brain - Hanson, Rick; Mendius, Richard; Sounds True (Firm) ([Boulder, CO] Sounds True, 2009)
Drawing on research spanning more than 30 years, collects meditative and contemplative practices to help increase the capacity for joy, love, and spiritual bliss.
Disc 1. Using your mind to change your brain ; How your mind and brain work together ; Why aren't people happier? ; The effects of meditation on your brain ; Guided meditation: appreciating your brain -- Disc 2. The four steps to taking in the good ; Guided meditation: taking in the good ; Introduction: antidote to stress ; Guided meditation: antidote to stress ; Introduction: healing painful experiences ; Guided meditation: healing painful experiences -- Disc 3. Introduction: steadying your mind ; Guided meditation: steadying your mind ; Introduction: mosaic meditation ; Guided meditation: mosaic meditation.
"Rewire your neural pathways to transform you life."--Container.
Duration: 3:30:00.
Presented by Rich Hanson & Richard Mendius.
Keywords: Meditation; Neuropsychology; Mind and body; Happiness; Meditation; Audiobooks